(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
The research attempts to find out the relation to reading and writing skill from grade 9 textbook. There are four basic skills i.e. listening, speaking, reading, and writing which are strongly prescribed in the textbook. Here, the researcher has tried to explore the two major skills, namely reading and writing and their relation while practicing in the textbook. This research uses descriptive qualitative research. The data source of this research is English textbook entitled ‘English 9’. The text has allotted marks for each skill in the syllabus. The reading text of grade 9 comprises 40% marks while writing comprises 35% of total marks. There are ten outcomes that are supposed to be achieved by students under the reading section. This number is equal in the writing section as well. By this, the course has adopted the sequential approach to reading and writing instruction, i.e. reading leading to writing. However, most of the contents given in the reading section do not collaborate with the writing part. There are ample examples where the students feel difficulties while producing the writing part given in the textbook. The collected data was interpreted using a descriptive approach. It was found that most of the tasks given in the textbook in relation to reading and writing are in segregated form. This idea of segregation is quite different from what the modern scholar say about skills of language learning.